Shared Renewable Resource and International Trade: Technical Measures for Resource Management - Yasuhiro Takarada; Weijia Dong; Takeshi Ogawa (European Regional Science Association (ERSA), 2011)
We examine trade and strategic interaction between countries that enforce technical measures for resource management which restricts capacity of exploitation to protect an internationally shared renewable resource. The technical measures are common management tools in fisheries (e.g., restrictions on gears, vessels, areas and time). We show that under bilateral resource management, the resource exporting country gains from trade, whereas trade causes steady state utility to fall in the resource importing country because the resource exporting country implements non-cooperative management when the demand for the harvest is not so high. Under sufficiently high demand for the harvest, maximum sustainable yield (MSY) can be attained after trade by what we call cooperative management and both countries are better off. Under low demand for the harvest, trade benefits the resource importing country but may harm the resource exporting country although it implements strict resource management which leads to MSY.
Keywords: 330